The renaissance of compulsory licenses (in the pharma sector) - Szupera, Blanka (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2023)
This paper examines the function of compulsory licensing of the manufacture of pharmaceutical products. The COVID-19 pandemic has challenged the pharmaceutical patents and the compulsory licenses in the pharmaceutical sector. In International law the TRIPS Agreement introduced a special possibility to use the subject matter of a patent without the authorization of the right holder. The development of this license was determined by the public health problems of the least-developed countries (hereinafter referred to as the LDCs). Today the global pandemic has challenged this system. Some developing countries proposed that the World Trade Organization temporarily shall waive intellectual property rights for COVID-19 vaccines. The legislation of some countries allowed the governance to order the limitations of patents, but such a solution could harm the legitimate interests of the patent owners. The global need for rapid treatment of COVID-19 showed that patentees cannot make pharmaceutical inventions sufficiently available on the market. There are other solutions like patent pools, by which patent owners could keep control of the use of their inventions and the patents would be still available for third parties. This would serve the general public interest, but it is a money and timeconsuming, long-distance cooperation. The broadened use of compulsory licensing could also expand vaccine manufacturing within the patent system. Hungary has chosen this path and the new legislation means the renaissance of compulsory licenses.